Gamma spectroscopy of even-even Ytterbium isotopes - Efstathiou, Margarita; Karadimas, Angelos; Zyriliou, Aikaterini; Vasileiou, Polytimos; Mertzimekis, Theodoros; Chalil, Achment; Pelonis, Stefanos (HNPS Advances in Nuclear Physics, 2023)
The even-even Ytterbium isotopes lack spectroscopic information with the increase of the neutron number and they are well deformed nuclei, presenting rotational properties. In this mass region of the nuclear chart predictions have shown rare phenomena related to nuclear structure, such as shape coexistence. In this work the population of excited states were investigated in the even-even Yb isotopes via the 2n-transfer reaction 168-174Yb (18O, 16O) 170-176Yb. The measurements were carried out at the 9 MV Tandem accelerator at the Horia Hulubei National Institute of Physics and Nuclear Engineering (IFIN-HH) in Romania. The deduced gamma-ray angular distributions in the ground state bands are found to correspond with transitions, as expected